Going Up the Country : Adventures in Blues Fieldwork in the 1960s - Bokelman, Marina; Evans, David, 1944- (Book collections on Project MUSE., 2022)
"At the height of the blues revival, Marina Bokelman and David Evans, young graduate students from California, made two trips to Louisiana and Mississippi and short trips in their home state to do fieldwork for their studies at UCLA. While there, they made recordings and interviews and took extensive field notes and photographs of blues musicians and their families. Going Up the Country: Adventures in Blues Fieldwork in the 1960s presents their experiences in vivid detail through the field notes, the photographs, and the retrospective views of these two passionate researchers. The book includes historical material as well as contemporary reflections by Bokelman and Evans on the times and the people they met during their southern journeys. Their notes and photographs take the reader into the midst of memorable encounters with many obscure but no less important musicians, as well as blues legends, including Robert Pete Williams, Mississippi Fred McDowell, Al Wilson (cofounder of Canned Heat), Babe Stovall, Reverend Ruben Lacy, and Jack Owens. This volume is not only an adventure story, but also a scholarly discussion of fieldwork in folklore and ethnomusicology. Including retrospective context and commentary, the field note chapters describe searches for musicians, recording situations, social and family dynamics of musicians, and race relations and the racial environment, as well as the practical, ethical, and logistical problems of doing fieldwork. The book features over one hundred documentary photographs that depict the field recording sessions and the activities, lives, and living conditions of the artists and their families. These photographs serve as a visual counterpart equivalent to the field notes. The remaining chapters explain the authors' methodology, planning, and motivations, as well as their personal backgrounds prior to going into the field, their careers afterwards, and their thoughts about fieldwork and folklore research in general. In this enlightening book, Bokelman and Evans provide an exciting and honest portrayal of blues field research in the 1960s"--